Spasticity evaluation with the Amadeo Tyromotion device in patients with hemispheric stroke - Urrutia, Rocío; Miren Gutiérrez-Muto, Ane; Sanz-Morère, Clara B.; Gómez, Arantxa; Politi, Angela M.; Lunardini, Francesca; Baccini, Marco; Cecchi, Francesca; León, Natacha; Oliviero, Antonio; Tornero, Jesús (Frontiers in Neurorobotics, 2023)
Objective: To verify the reliability and the concurrent and discriminant validity of the measurements of spasticity offered by the robotic device, quantifying the 1) test-retest reliability, 2) correlation with the clinical evaluation using the Modified Ashworth Scale (MAS), 3) inter-rater reliability between the two physiotherapists and 4) ability to discriminate between healthy and stroke patients. Methods: Twenty stroke patients and twenty healthy volunteers participated in the study. Two physical therapists (PT1 and PT2) independently evaluated the hand spasticity of stroke subjects using the MAS. Spasticity was assessed, both in healthy and in stroke participants, with the Amadeo device at three increasing velocities of passive movement for three consecutive repeated assessments, while raw data of force and position were collected through an external program. Data analysis: The Intraclass Correlation Coefficient (ICC) and the weighted kappa were computed to estimate the reliability of the Amadeo device measurements, the inter-rater reliability of MAS, and the correlation between the MAS and the Amadeo device measures. The discriminant ability of the Amadeo device was assessed comparing the stroke and healthy subjects’ spasticity measures with the percentage of agreements with 0 in MAS for healthy subjects. Results: The test-retest reliability of the Amadeo device was high with ICC at all the three velocities (ICC=0.908, 0.958, and 0.964, respectively); but lower if analyzed with weighted kappa correlation (0.584, 0.748, and 0.749 as mean values for each velocity, respectively. The correlation between Amadeo and the clinical scale for stroke patients with weighted kappa correlation was poor (0.280±0.212 for PT1 and 0.290±0.155 for PT2). The inter-rater reliability of the clinical MAS was high (ICC=0.911). Conclusion: Both MAS and Amadeo spasticity scores showed good reliability. The Amadeo scores did not show strong clinical correlation with the MAS in stroke patients. Hitherto, Amadeo evaluation shows trends that are consistent with the characteristics of spasticity, such as an increased in spasticity as the speed of muscle stretching increases. The ability of the device to discriminate between stroke patients and healthy controls is low. Future studies adopting an instrumental gold standard for spasticity may provide further insight on the validity of these measures.